Patient satisfaction and associated factors among in-patients in Primary Hospitals of North Shoa Zone, Amhara Regional State, Ethiopia - Zenebe Wondimhunegn Weldearegay; Sisay Shewasinad Yehualahet; Shimelse Ololo Sinkie; Tilahun Fufa Debela (International Journal of Public Health Science (IJPHS), 2020)
Satisfaction of patient is the preferred item for the consumption of care. It is related to health services consumption. The objective of the study was to determine the level of patient satisfaction and associated factors among patients Primary Hospitals of North Shoa Zone. Institutional-based cross-sectional study design were implemented from March 15-April 25, 2019. Sample sizes of 422 inpatients were included. Participants were selected by lottery method. Factor analysis was used in order to generate factor scores for further analysis. Variables P<0.25 on the bivariate analysis were included in the multiple linear regression and variables with p<0.05 with 95% confidence interval were considered as statistically significant. There was 59.1% inpatient was satisfied. Sex, religion, place of residence, previous admission and occupational status of a housewife, ggovernment employee and educational status of primary school were associated with patient satisfaction.